PENINGKATAN MUTU AUDIT DALAM MENGHADAPI KECURANGAN PERUSAHAAN - Martok, Yenni (Jurnal Mahkota Bisnis (Makbis), 2024)
Fraud often occurs during the preparation of financial reports, where it is defined as a deliberate error or omission in the review or disclosure of financial statements. Implementing an audit system to prevent fraud in financial reporting is an essential task and responsibility of auditors. Auditors are required to present their findings clearly, transparently, and without ambiguity, demonstrating that they have considered the possibility of fraud and explaining the methods used in their examination. Additionally, auditors must be ready to act as internal controllers, utilizing their expertise and knowledge through the audit system to identify and address fraud within the organization during the recording of financial reports.